2019
DOI: 10.1094/pdis-02-18-0370-re
|View full text |Cite
|
Sign up to set email alerts
|

Pectobacterium carotovorum subsp. brasiliense Causes Soft Rot and Death of Neobuxbaumia tetetzo in Zapotitlan Salinas Valley, Puebla, Mexico

Abstract: Neobuxbaumia tetetzo (Coulter) Backeberg (tetecho) is a columnar cactus endemic to Mexico. Tetecho plants, flowers, fruits, and seeds play an important role in the semiarid ecosystem, as they serve as a refuge and food for insects, bats, and birds, and are widely used by ethnic groups since pre-Hispanic times. Tetecho is affected by a soft rot that damages the whole plant and causes its fall and disintegration. Eight bacterial colonies of similar morphology were isolated from plants showing soft rot and inocul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 29 publications
1
4
0
1
Order By: Relevance
“…Control plants inoculated with LB medium remained healthy during the time of the experiment (Fig 4). Taken together, these results confirm that strains A1, A3 and A8 recapitulate in vitro the disease symptoms observed in wild tetecho cacti, and they point to Pectobacterium as the ethiological agent, in agreement to previous observations [6].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Control plants inoculated with LB medium remained healthy during the time of the experiment (Fig 4). Taken together, these results confirm that strains A1, A3 and A8 recapitulate in vitro the disease symptoms observed in wild tetecho cacti, and they point to Pectobacterium as the ethiological agent, in agreement to previous observations [6].…”
Section: Resultssupporting
confidence: 91%
“…We have preoviusly reported that P. brasiliense causes soft rot in N. tetetzo [6], but here we aimed to analyse new isolates in more detail. Using potatoes as baits to collect samples of three diseased and healty individuals we confirmed rot of potatos inoculated with infected cactus tissue while potatoes inoculated with healthy tissue did no rot.…”
Section: Resultsmentioning
confidence: 99%
“…atrosepticum has been isolated from potato, D. chrysanthemi from carrot and P. carotovorum from nopal (Opuntia cacti) (Oliveira et al 2003;González-Rodríguez et al 2005). Recently, P. brasiliense was described as the causative agent of soft rot of cactus crops in México (Mejía-Sánchez et al 2019). Ribas (2007) described pre-harvest field losses of potato crops in the field due to damage caused by Pectobacterium spp.…”
Section: Mexicomentioning
confidence: 99%
“…The P. carotovora subsp. brasiliense is distributed worldwide and reported to cause blackleg of potato in South Africa (Van der et al, 2010), Kenya (Onkendi & Moleleki, 2014), Switzerland (De Werra et al, 2015), Turkey (Ozturk & Aksoy, 2016), Netherlands (van der Wolf et al, 2017), soft rot of pumpkin in Austria (Gottsberger & Huss, 2016), stem rot of tomato in Italy (Caruso et al, 2016), soft rot of cucumber (Meng et al, 2017) and radish in China (Liu et al, 2019), on squash and watermelon in Siberia (Zlatkovic et al, 2019) and Neobuxbaimia tetetzo in Mexico (Mejía‐Sánchez et al, 2019).…”
Section: Introductionmentioning
confidence: 99%